2006
DOI: 10.1111/j.1744-9987.2006.00427.x
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of 2‐Arachidonoylglycerol Action by Direct Hemoperfusion Through Immobilized Polymyxin B Fibers: An Experimental Study in Conscious Guinea Pigs

Abstract: Direct hemoperfusion through a network of immobilized polymyxin B fibers is used for the treatment of septic shock, but the mechanism underlying the clinical benefits remains unclear. The aims of the present study were to assess the actions of direct hemoperfusion through immobilized polymyxin B fibers on effects of exogenous endotoxin or 2-arachidonoylglycerol in conscious guinea pigs; and to examine the underlying mechanisms. In the present study, colonic motion was monitored continuously by telemetry using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…The post‐LPS decreases in intestinal tension and blood pressure have been reported to peak approximately 2 h after LPS administration; this effect has been shown to be mediated by the type 1 cannabinoid (CB 1 ) receptor 18–20 . Lipopolysaccharide acts on macrophages and monocytes through toll‐like receptor 4 (TLR4) 21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The post‐LPS decreases in intestinal tension and blood pressure have been reported to peak approximately 2 h after LPS administration; this effect has been shown to be mediated by the type 1 cannabinoid (CB 1 ) receptor 18–20 . Lipopolysaccharide acts on macrophages and monocytes through toll‐like receptor 4 (TLR4) 21 .…”
Section: Discussionmentioning
confidence: 99%
“…The post-LPS decreases in intestinal tension and blood pressure have been reported to peak approximately 2 h after LPS administration; this effect has been shown to be mediated by the type 1 cannabinoid (CB 1 ) receptor. [18][19][20] Lipopolysaccharide acts on macrophages and monocytes through toll-like receptor 4 (TLR4). 21 The signals mediated by TLR4 result in the increased synthesis and release of 2-arachidonoyl glycerol, an endocannabinoid, which results in smooth muscle relaxation, specifically of the colon and blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…LPS, which is a ligand for the Toll-like receptor 4 (TLR4), binds to TLR4 on the cell membrane and transmits a signal that results in production of mediators such as endocannabinoids, nitric oxide (NO), and cytokines, which initiate immune reactions 13) . Endogenous cannabinoids have wide-ranging physiological activities, including the relaxation of intestinal smooth muscles [14][15][16] and vascular smooth muscles 2,16) . Both of these reponses are elicited by the CB1-R, but not the CB2-R. LPS is reported to induce the NO-mediated responses of decreased gastrointestinal transit 17) , and decreased ileal muscle contractility 18) and blood vessel relaxation 19) .…”
Section: Discussionmentioning
confidence: 99%
“…For such severe endotoxaemia, PMX treatment was clearly effective and significantly improved survival rates. PMX treatment removes LPS and LPS-induced endocannabinoids 5,12) . Endocannabinoids, particularly 2-arachidonylglycerol (2-AG), are attracting attention as early initial mediators of sepsis 17,18) .…”
Section: Effects Of Pmx And/or Sivelestat On Lps-induced Increases Inmentioning
confidence: 99%
“…have reported that LPS administration induces the production of 2-AG, leading to paralytic ileus mediated by cannabinoid (CB)-1 receptors. It has been shown that the elimination of 2-AG by polymyxin B immobilized fiber-direct hemoperfusion (PMX-DHP) reduces paralytic ileus 5) . In cases of patients with increased blood pressure resulting from PMX-DHP treatment, the plasma concentration of 2-AG was decreased 6,7) .…”
Section: Introductionmentioning
confidence: 99%